Generic Attitude Research: Finding Creative Attitude Function in Consumer Marketing Over Katz Theory – A Theoretical Study - Prasanta Biswas (AG Volumes, 2022)
Individual prospect usually makes an attitude after having a contact with product/service, as proposition. To make a success in marketing programme, marketer gives best attempt to achieve a ‘desired’ attitude. Ultimate target is to be a purchasing behaviour as an output of marketing. With purview of consumer behaviour & its marketing management, there is the conventional theory, called as Katz theory of attitude function, so fundamental so traditional, making helpful to this present study to undergo. For an objective pursuit to arrive at, seven (7) attitudes have been obtained by implying ‘creative’ nature on its methodology. These attitudes by function could be regarded as attitude function of future vision also, almost to any marketing scenario. It provides enhancement through an intense association with consumer’s decision making (which is, building up of ‘attitude’ function) to purchasing. Such ‘creative’ attitude functions, known as C.C.A in study, are very specific to the kind & get engaged in instantly whence a consumer is actually seeing an advertisement or going through a media publicity, of a proposition. Consumer marketing would get better efficient ladder over such ‘creative’ attitude functions in order to create better, specific, ‘engaging & intense’ proposition ‘persuasion’ among prospects. This study shows the path to explore out many of ‘creative’ ones as attitude function as to research point of interest.